The different maturation of the corticospinal tract and corticoreticular pathway in normal brain development: diffusion tensor imaging study - Yeo, Sang Seok; Jang, Sung Ho; Son, Su Min (Frontiers in Human Neuroscience, 2014)
Background and Purpose: The corticospinal tract (CST) and corticoreticular pathway (CRP) are known to be important neural tracts for motor development. However, little is known about the difference in maturation of the CST and CRP. In this study, using diffusion tensor imaging (DTI), we investigated maturation of the CST and CRP in typically developed children and normal healthy adults. Methods: We recruited 75 normal healthy subjects for this study. Diffusion tensor imaging was performed using 1.5-T, and the CST and CRP were reconstructed using DTI-Studio software. Values of fractional anisotropy (FA) and fiber volume (FV) of the CST and CRP were measured. Results: In the current study, the threshold points for CST and CRP maturation were different in normal brain development. Change in FA value of the CST showed a steep increase until seven years of age and then a gradual increase until adulthood, however, the CRP showed a steep increase only until two years of age and then a very gradual increase or plateau until adulthood. In terms of FV, the CST showed a steep increase until 12 years and then a gradual increase until adulthood, in contrast, the CRP showed gradual increase of FV across whole age range (0-25 years). Conclusion: The difference in maturation process between CST and CRP appears to be related to different periods of fine and gross motor development. This radiologic information can provide a scientific basis for understanding development in motor function.